PENGARUH GAYA KEPEMIMPINAN DAN PEMBERIAN KOMPENSASI TERHADAP KEPUASAN KERJA SERTA IMPLIKASINYA TERHADAP KINERJA KARYAWAN PT.MAXIMA ARTA JAKRTA - Rudi Bratamanggala; Habibatul Munawaroh (Jurnal Manajemen FE-UB, 2018)
The data used in this study in the form of primary data collected from respondents' answers based on questionnaires given, as many as 80 people. Data processing method uses Path Analysis method with the help of SPSS version 22.0. The statistical test used the significance test of individual parameters (t test) and simultaneous significance test (Test F).The results showed that simultaneously variable of leadership style, giving of compensation and job satisfaction have a significant effect on employee performance. Partially show that analysis 1: leadership style variables significantly influence employee performance, while analysis 2: compensation variable significantly influence employee performance and in analysis 3: job satisfaction variables have a significant effect on employee performance. Keywords: leadership style, giving compensation, job satisfaction and employee performance